Environmental awareness study on the geographical perspective of Kedah and Kelantan communities in Malaysia - Saudi, Mohd Haizam; Umar, Narul Rahimah; Kamarudin, Mohd Khairul Amri; Musa, Nur Fatin Farahhana; Mohd Nor, Siti Nor Shahira; Mohd Saudi, Ahmad Shakir; Abu Samah, Mohd Armi; Abdul Maulud, Khairul Nizam; Hamzah, Firdaus Mohamad; Md Bati, Siti Nor Aisyah (Eskisehir Osmangazi University, 2021)
Environmental pollution is a problem that occurs all over the country and it has different effects on human health. The issue of pollution is a new challenge for urban and rural residents. This study aims to analyze environmental awareness among the geographical perspective of Kedah and Kelantan communities in Malaysia. The method used in this study is quantitative method. This study was conducted on 500 responders from urban and rural area in Kedah and Kelantan, Malaysia. Data were collected using questionnaires and analyzed to measure the level of environmental awareness among communities in Kedah and Kelantan. The data obtained were analyzed using XLStat2020. The data shows that the level of awareness in Kedah and Kelantan is still at an encouraging level. This study showed that urban and rural population in Kedah and Kelantan experienced in environmental awareness with a significant value of 0.05. Therefore, environmental education is the best effort to maintain public awareness of environmental care.